2011
DOI: 10.1016/s0924-9338(11)73929-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural telepsychiatry and its impact on patient satisfaction

Abstract: IntroductionNational and International telepsychiatry service was established between Denmark and Sweden in order to increase access to cross-cultural expertise. Patient acceptability study was conducted to assess the patients’ attitudes toward the quality, advantages and disadvantages of telepsychiatry service.MethodsOver a period January 2005-December 2007, 61 patients were treated via telepsychiatry by clinicians that speak patientsrespective mother tongues. Video-conferencing equipment connected the Little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 0 publications
1
45
0
Order By: Relevance
“…None of the studies in this review mentioned the use of interpreters; their incorporation into telepsychiatry, whether for Makaton, other forms of signing or in fact more mainstream language translation, is another potential avenue of research. 40,41 It is feasible that access to expertise via international collaborations using asynchronous methods or taking advantage of time zone differences for synchronous methods could enable, for example, vulnerable intellectual disability populations in underserved areas to access specialist intellectual disability psychiatric care to aid in reducing mental distress. Additional health economic and environmental evaluations in differing healthcare systems could also clarify whether similar models of care are transposable to such systems.…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies in this review mentioned the use of interpreters; their incorporation into telepsychiatry, whether for Makaton, other forms of signing or in fact more mainstream language translation, is another potential avenue of research. 40,41 It is feasible that access to expertise via international collaborations using asynchronous methods or taking advantage of time zone differences for synchronous methods could enable, for example, vulnerable intellectual disability populations in underserved areas to access specialist intellectual disability psychiatric care to aid in reducing mental distress. Additional health economic and environmental evaluations in differing healthcare systems could also clarify whether similar models of care are transposable to such systems.…”
Section: Discussionmentioning
confidence: 99%
“…Immigrants and refugees, as well as minority communities in remote areas have a difficulty to access culturally sensitive mental health provider, and in native language. One of the benefits of telepsychiatry could be in connection between psychiatrist and patient whom speak the same language, and have a similar cultural background [77][78][79][80] .…”
Section: Military Populations International Settings and Cultural Cmentioning
confidence: 99%
“…However, other more longitudinal studies corroborate the suggestion that the acceptability of telepsychiatry is associated with adherence to therapy, even in culturally isolated populations. 1,6 For example, in 2010, Mucic showed that in a study of refugees and asylum seekers that there was a high level of satisfaction with telepsychiatric care, and that the participants completed an average of five sessions during the study period. 6 Of course, after confirming acceptability to patients and likelihood of patient adherence, the next step in implementing telepsychiatry is analysis of long-term patient outcomes.…”
mentioning
confidence: 99%
“…1,6 For example, in 2010, Mucic showed that in a study of refugees and asylum seekers that there was a high level of satisfaction with telepsychiatric care, and that the participants completed an average of five sessions during the study period. 6 Of course, after confirming acceptability to patients and likelihood of patient adherence, the next step in implementing telepsychiatry is analysis of long-term patient outcomes. A review of one useful metric, readmission rates, was recently conducted by Koblauch et al It was demonstrated that results of studies measuring readmission after telepsychiatry compared to traditional modalities of care have been mixed; some report a reduction in rate, while others show no difference.…”
mentioning
confidence: 99%